Wanna try something crazy? - Chia, Chester Wei-Ze (Nanyang Technological University, 2023)
Wanna Try Something Crazy? is a 3D animated short film project that was crafted over two semesters by a talented team of four: Chester Chia Wei-Ze, Tan Ying Jian, Charmaine Tee and Jerome Tan Zhi Rong. The film showcases keyframe animation with an artistic, painting-inspired aesthetic, using flat, hand-painted backgrounds projected onto 3D-modelled environments. Visual effects are created using both frame-by-frame 2D painted effects and motion graphics.